Growth kinetics and thermodynamic stability of octadecyltrichlorosilane self-assembled monolayer on Si (100) substrate - Kulkarni, S. A.; Mirji, S. A.; Mandale, A. B.; Gupta, R. P.; Vijayamohanan, K. P. (Materials Letters, 2005)
We have studied the growth kinetics and thermodynamic stability of octadecyltrichlorosilane (OTS) self-assembled monolayers on Si (100) substrate in order to understand its role in controlling the adhesion and surface hydrophobicity. Time-dependent contact angle measurements, using water as a function of OTS concentration, show rapid monolayer formation in the initial stage followed by a slow attainment of full coverage and the overall kinetics approximately follows the Langmuir adsorption isotherm. The adsorption rate constant (k(a) = 150 M-1 s(-1)) is found to be significantly greater than the desorption rate constant (k(d) = 0.156 s(-1)) while the Gibbs free energy (Delta G(ads)) change amounts to -4.2 kcal/mol suggesting thermodynamic stability of OTS monolayer on a silicon surface. Partial monolayer formation by a `uniform' growth mechanism, even at low coverage, is revealed by atomic force microscopy (AFM) in conjunction with grazing angle FTIR spectroscopy. Analysis of the interfacial adhesion properties using Zisman plot suggests a critical surface tension (gamma(c)) of 20.7 dyn/cm for OTS monolayer on Si (100) surface. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Gibbs's free energy (AG); growth kinetics; octadecyltrichlorosilane (OTS); self-assembled monolayers (SAMs); Zisman plot